2009
DOI: 10.1517/13543770902766829
|View full text |Cite
|
Sign up to set email alerts
|

A new class of UDP-3-O-(R-3-hydroxymyristol)-N-acetylglucosamine deacetylase (LpxC) inhibitors for the treatment of Gram-negative infections: PCT application WO 2008027466

Abstract: The LpxC inhibitors disclosed in PCT application WO 2008027466 contain hydantoins in place of the hydroxamic acids commonly found in most previously described inhibitors. These molecules could represent a means of treating Gram-negative infections via a more selective inhibition of LpxC.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 20 publications
0
12
0
Order By: Relevance
“…[107][108] The inhibition of one of the first six enzymes of Kdo2-Lipid A synthesis has been shown to be lethal for E. coli [109][110] and/or renders the bacteria susceptible to other antibiotics that normally do not penetrate the outer membrane. 41,107,[111][112] Thus, the strategy of identifying new Lpx inhibitors has a vital role in the development of new antimicrobial agents. 107  LpxA UDP-N-acetylglucosamine acyltransferase or LpxA is the first enzyme of LPS biosynthesis pathway that catalyzes the reversible transfer of R-3-hydroxy-acyl moiety from its donor acyl carrier protein (ACP) thioester to the UDP-N-acetyl-glucosamine.…”
Section: Lps and Antibiotic Resistancementioning
confidence: 99%
See 1 more Smart Citation
“…[107][108] The inhibition of one of the first six enzymes of Kdo2-Lipid A synthesis has been shown to be lethal for E. coli [109][110] and/or renders the bacteria susceptible to other antibiotics that normally do not penetrate the outer membrane. 41,107,[111][112] Thus, the strategy of identifying new Lpx inhibitors has a vital role in the development of new antimicrobial agents. 107  LpxA UDP-N-acetylglucosamine acyltransferase or LpxA is the first enzyme of LPS biosynthesis pathway that catalyzes the reversible transfer of R-3-hydroxy-acyl moiety from its donor acyl carrier protein (ACP) thioester to the UDP-N-acetyl-glucosamine.…”
Section: Lps and Antibiotic Resistancementioning
confidence: 99%
“…41,[128][129][130][131] LpxC requires one or more zinc ions to be catalytically active and NMR and X-ray crystallography studies indicate that LpxC has a "β-α-α-β sandwich" structure and encapsulates the acyl chain of the substrate with a unique hydrophobic passage. 112,132 Many potent LpxC inhibitors have been identified, most of which contain a hydroxamate group that targets the catalytic zinc ion. [133][134][135][136][137] In the late 1980s, screening achieved by Merck research laboratories identified the small oxazoline hydroxamic acid compound 16 (Figure 7) which exerts antimicrobial activity against E. coli strains with MIC values ranging from 200 to 400 µg/mL by inhibiting Lipid A synthesis and LPS production.…”
Section: Lpxc Inhibitorsmentioning
confidence: 99%
“…13,19,24,[27][28] However, in the case of LpxC inhibitors, only a few inhibitors that do not contain the Zn 2+ -chelating hydroxamate moiety have been reported so far. [29][30][31][32][33][34][35][36][37] Recently, we have reported on a series of benzyloxyacetohydroxamic acids as inhibitors of LpxC, with the most potent compound, 3 (Figure 1), exhibiting promising activities in the enzyme assay (IC50 = 0.48 µM, Ki = 66 nM) as well as in the performed disc diffusion assays (Table 1). 38 Therefore, the compound should be further investigated.…”
Section: Introductionmentioning
confidence: 99%
“…27 Several earlier studies demonstrate that UDP-3-O-[(R)-3-hydroxymyristoyl]-N-acetyl glucosamine deacetylase (LpxC) as an essential enzyme in virtually all Gram-negative bacteria and it is a paramount significant target for treatment of multidrug-resistant Gram-negative infections. 6,11,20,46 LpxC is Zn 2+ -dependent metalloamidase uses Zn 2+ to activate a nucleophilic attack by water on the amide of the Nacetylglucosamine (GlcNAc) moiety of the substrate in the hydrophobic tunnel of active site 3 ; it catalyzes the second committed, irreversible step of biosynthesis of lipid-A required for cell wall formation.…”
Section: Introductionmentioning
confidence: 99%
“…For instance, the literature reports that previously described LpxC inhibitors contain a hydroxamic acid which lead to unwanted side effects. 6 Thereby, to overcome the challenges of adverse chemical reactions of developing drugs, common LpxC should intensively be investigated to permit the development of H. pylori selective therapeutic agents. 20 An adept therapeutic design has become an attractive choice in the development of the novel antibiotic therapy over the present conventions for deconvoluting the complexities of molecular pharmacology.…”
Section: Introductionmentioning
confidence: 99%